1992
DOI: 10.1111/j.1365-2249.1992.tb07948.x
|View full text |Cite
|
Sign up to set email alerts
|

Passive immunization against tumour necrosis factor-alpha (TNF-α) and IL-lβ protects from LPS enhancing glomerular injury in nephrotoxic nephritis in rats

Abstract: SUMMARYGlomerular injury caused by injection of heterologous anti-glomerular basement membrane antibodies (anti-GBM Ab) is increased in rats pretreated with small doses of bacterial lipopolysaccharide (LPS). We have Investigated the involvement of tumour necrosis factor-alpha (TNF-a), IL-la and IL-l^in this phenomenon by passive immunization against these cytokines. Anti-TNF-«oranti-IL-l/i antibodies given 15 h before the induction of nephritis significantly decreased injury in this model, whether assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 33 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…Studies in murine crescentic glomerulonephritis (GN) indicate that IL-1β is the major proinflammatory cytokine-mediating glomerular injury [20]. The benefits of inhibiting IL-1 using anti-IL-1 antibodies [21], soluble IL-1 receptor, or IL-1-receptor antagonist [22] have been shown in experimental GN. Our data revealed that increasing IL-1β expression accompanied severe glomerulosclerosis and renal tubular cell injury in untreated ADR-nephrosis rats, whereas mild and moderate glomerulosclerosis and renal tubular cell injury with weak IL-1β expression were found in the renal tissue of simvastatin-treated ADR-nephrosis rats.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in murine crescentic glomerulonephritis (GN) indicate that IL-1β is the major proinflammatory cytokine-mediating glomerular injury [20]. The benefits of inhibiting IL-1 using anti-IL-1 antibodies [21], soluble IL-1 receptor, or IL-1-receptor antagonist [22] have been shown in experimental GN. Our data revealed that increasing IL-1β expression accompanied severe glomerulosclerosis and renal tubular cell injury in untreated ADR-nephrosis rats, whereas mild and moderate glomerulosclerosis and renal tubular cell injury with weak IL-1β expression were found in the renal tissue of simvastatin-treated ADR-nephrosis rats.…”
Section: Discussionmentioning
confidence: 99%
“…There is a mounting evidence to implicate TNF-in the pathogenesis of glomeruli of rodents with experimental nephritis, and is found in renal biopsies, sera and urine of patients with different types of glomerulonephritis [88][89][90][91]; In vitro and in vivo studies document that TNF-is produced locally within inflamed glomeruli by mesangial and epithelial cells, as well as by infiltrating monocytes/macrophages [89,91]; Systemic administration of TNFresults in glomerular damage in rabbits [92] and exacerbates the degree of glomerular injury in nephrotoxic nephritis in rats [93]; and blocking endogenous TNF-in nephrotoxic nephritis in rats ameliorates acute glomerular inflammation [94], and down-regulates glomerular IL-1 mRNA and circulating TNF-concentrations [95].…”
Section: Discussionmentioning
confidence: 99%
“…Very interesting is the ability to simultaneously inhibit TNF and IL-1, then it is because most of the two cytokines produced by monocytes-macrophages and mesangial cells during activation by immune-mediated GN [67]. At present, the combined use of the two drugs was too burdened by side effects [13,58,59].…”
Section: Anti-il-1mentioning
confidence: 99%
“…Another approach theoretically very interesting is the use of cytokines that act naturally against the inflammatory process, such as IL -4, IL -1 0 , IL-13 or modest doses of TG -ß1 [58,67,68].…”
Section: Use Of Anti-inflammatory Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation